Relative age of youth swimmers and their sporting performance at the end of the season - Mendoza-Castejón, D.; Trinidad, A.; De la Calle, L. M.; Belando-Pedreño, N. (PLOS ONE, 2025)
This study explores the influence of relative age on the athletic and academic performance of young swimmers, while also considering other contributing factors such as training conditions, anthropometric characteristics, and coaches` subjective evaluations. A descriptive, explanatory, and prospective design was employed, using quantitative (questionnaires) and observational methods. The sample consisted of 33 national-level swimmers (11 males and 22 females). Variables analyzed included sex, date of birth, training data, academic performance (AP), final sport performance (SP), coaches` perceptions of daily performance, and anthropometric measurements. Results indicated no direct effect of relative age on the main variables. However, ANCOVA revealed significant differences based on birth quartile (p = .001), month of birth (p = .001), training frequency (p = .003), and body weight when mediated by sport category. Additionally, significant associations were found between relative age and sport performance when BMI was included as a covariate (p = .036), along with year and month of birth (p = .038; p = .027). Coaches` perceptions of performance were also significantly related to competitive category (p = .033). It is concluded that while relative age may influence athletic performance, its effect appears to be mediated by contextual and individual factors related to the athlete`s preparation and environment.